2013
DOI: 10.1097/phh.0b013e31828000de
|View full text |Cite
|
Sign up to set email alerts
|

State-Level Tobacco Control and Adult Smoking Rate in the United States

Abstract: Consistent with previous literature, taxation and smoking restrictions have the most immediate statewide impacts on smoking rate. Probusiness/antitax politics and tobacco manufacturing affect level of implementation of these and other effective TCMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
2
11
1
Order By: Relevance
“…These cultures have been associated with different patterns of government intervention, levels of social inequality, as well as health outcomes (Sharkansky, 1969). Morley and Pratte (2013), for example, showed that Republican control of state legislatures was associated with lower excise taxes on cigarettes which in turn were significant predictors of state smoking rates.…”
Section: Regional Contextual Effects On Smokingmentioning
confidence: 98%
See 1 more Smart Citation
“…These cultures have been associated with different patterns of government intervention, levels of social inequality, as well as health outcomes (Sharkansky, 1969). Morley and Pratte (2013), for example, showed that Republican control of state legislatures was associated with lower excise taxes on cigarettes which in turn were significant predictors of state smoking rates.…”
Section: Regional Contextual Effects On Smokingmentioning
confidence: 98%
“…Consequently few studies have examined the association between state or regional factors and the likelihood of being a current smoker. With few exceptions (e.g., Hoffer and Pellilo, 2012;Morley and Pratte, 2013), this has been particularly true on how economic reliance on the tobacco industry has shaped local tobacco control policies and the incidence of smoking. The few studies that have been conducted have been largely confined to the Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/healthplace United States and have shown how the tobacco lobby has been detrimental to tobacco control and a reduction of smoking rates in those states where the industry is most powerful.…”
Section: Introductionmentioning
confidence: 97%
“…In the United Kingdom, conservative governments opposed tobacco control regulation between 1979 and 1997, while subsequent Labour governments introduced a range of measures which resulted in the United Kingdom becoming Europe's tobacco control leader (Asare, Cairney, & Studlar, 2009). In the United States, associations are found between Republican dominance at state level and lower cigarette taxes (Morley & Pratte, 2013), and between a legislator's being Republican and his or her intention to vote against tobacco taxes (Flynn et al, 1998). In Europe, in the period between 1996 and 2003, left-wing governments were more likely to adopt tobacco control measures than were right-wing governments (Bosdriesz, Willemsen, Stronks, & Kunst, 2014).…”
Section: Left-right Orientation Of the Governmentmentioning
confidence: 93%
“…Negative correlations between state cigarette price and smoking were observed in all states examined (Table 3) Numerous studies have demonstrated the impact of cigarette price on smoking and concluded that higher cigarette taxes lead to higher prices that discourage smoking initiation, promote cessation, prevent relapse among former smokers, and lower the number of cigarettes consumed by continuing smokers 1,[10][11][12][13][14][15][16][17][18][19][20][23][24][25][26] . Higher taxes also provide governments with finances that can be used to implement other proven tobacco control policies that further reduce smoking and improve public health 10,11,17,24,26 .…”
Section: Resultsmentioning
confidence: 99%
“…Raising cigarette excise taxes is however controversial with proponents claiming higher taxes reduce consumption and improve public health, while opponents claim they have a negative impact on the economy. Overwhelming studies nevertheless support this intervention, noting that it increases the cost of cigarettes, prevents smoking initiation, promotes cessation, and reduces the prevalence and intensity of smoking among youth and adults 1,[10][11][12][13][14][15][16][17][18][19][20] . Fewer people smoking means reduced risk of exposure to second-hand smoke (SHS) and associated illnesses, thus improved public health 10 .…”
Section: Introductionmentioning
confidence: 99%